2021
DOI: 10.1002/asi.24491
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge creation through collaboration: The role of shared institutional affiliations and physical proximity

Abstract: This paper examines how shared affiliations within an institution (e.g., same primary appointment, same secondary appointment, same research center, same laboratory/facility) and physical proximity (e.g., walking distance between collaborator offices) shape knowledge creation through biomedical science collaboration in general, and interdisciplinary collaboration in particular. Using archival and publication data, we examine pairwise research collaborations among 1,138 faculty members over a 12-year period at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…As indicated by the colors, four major clusters can be identified here. The higher degree of collaboration between authors of the same institutional affiliation is already well documented [53] and attributed to higher interpersonal connections and pure physical proximity. It is also evident here with collaborations between all prominent researchers from the Beijing University of Post and Telecommunication.…”
Section: Citation Impactmentioning
confidence: 68%
“…As indicated by the colors, four major clusters can be identified here. The higher degree of collaboration between authors of the same institutional affiliation is already well documented [53] and attributed to higher interpersonal connections and pure physical proximity. It is also evident here with collaborations between all prominent researchers from the Beijing University of Post and Telecommunication.…”
Section: Citation Impactmentioning
confidence: 68%
“…Research by Ertug et al (2022) found that homophily accelerates the transmission of information and influences behavior. Studies have also shown that academics are more likely to form associations and bonds with others who are similar to them in terms of their academic background and research interests (Stephens & Cummings, 2021). Therefore, we hypothesize that a close association of individuals in academic workgroups would influence the needs and requirements of the task and, thus, the perceived usefulness of AI chatbots.…”
Section: Homophilymentioning
confidence: 94%
“…Özellikle aktörler arasında temasın sağlanması ve bunun artırılması, karşılıklı güven ve anlayışın geliştirilmesi ve özellikle koordinasyon sorunlarının azaltılması coğrafi yakınlığın önemli olduğu sonucuna ulaşılmıştır. Bu nedenle bilimsel iş birliklerinin geliştirilmesinde ve disiplinler arası iş birliğinin teşvik edilmesi için gerekli planlama ve politika süreçlerinde coğrafi yakınlığın dikkate alınması önerilmektedir (Stephens & Cummings, 2021). Peki, coğrafi yakınlık bütün bu süreçlerin gelişmesi için yeterli midir?…”
Section: Bi̇lgi̇ni̇n Yayilmasi Ve Araştirma İş Bi̇rli̇kleri̇ni̇n Gel...unclassified